Rescue of amyotrophic lateral sclerosis phenotype in a mouse model by intravenous AAV9‐ADAR2 delivery to motor neurons - Takenari Yamashita; Hui Lin Chai; Sayaka Teramoto; Shoji Tsuji; Kuniko Shimazaki; Shin‐ichi Muramatsu; Shin Kwak (EMBO Molecular Medicine)
Abstract Amyotrophic lateral sclerosis (ALS) is the most common adult‐onset motor neuron disease, and the lack of effective therapy results in inevitable death within a few years of onset. Failure of GluA2 RNA editing resulting from downregulation of the RNA‐editing enzyme adenosine deaminase acting on RNA 2 (ADAR2) occurs in the majority of ALS cases and causes the death of motor neurons via a Ca2+‐permeable AMPA receptor‐mediated mechanism. Here, we explored the possibility of gene therapy for ALS by upregulating ADAR2 in mouse motor neurons using an adeno‐associated virus serotype 9 (AAV9) vector that provides gene delivery to a wide array of central neurons after peripheral administration. A single intravenous injection of AAV9‐ADAR2 in conditional ADAR2 knockout mice (AR2), which comprise a mechanistic mouse model of sporadic ALS, caused expression of exogenous ADAR2 in the central neurons and effectively prevented progressive motor dysfunction. Notably, AAV9‐ADAR2 rescued the motor neurons of AR2 mice from death by normalizing TDP‐43 expression. This AAV9‐mediated ADAR2 gene delivery may therefore enable the development of a gene therapy for ALS.